A cross-sectional study of bovine tuberculosis in the transhumant and agro-pastoral cattle herds in the border areas of Katakwi and Moroto districts, Uganda - Inangolet, F. O.; Demelash, B.; Oloya, J.; Opuda-Asibo, J.; Skjerve, E. (Tropical animal health and production, 2008)
A study to determine the prevalence of bovine tuberculosis in the transhumant and agropastoral cattle herds in the border areas of Katakwi and Moroto districts in Uganda was carried out from July 2006 to January 2007 using comparative intradermal tuberculin test containing bovine and avian PPDs. A total of 1470 animals, 612 (41.6%) males and 858 (58.4%) females, 883 (60%) young, 555 (37.8%) adult and 32 (2.2%) old animals were included. The study involved a cross-sectional multistage sampling technique with random selection of individual animals from a herd.
Keywords: PPD tuberculin reactors; Bovine tuberculosis; Cattle; Katakwi; Moroto; Uganda